Taxonomic studies in Wedelia (Asteraceae, Heliantheae) reveal a new species for the Brazilian Cerrado - De A. Bringel Jr., João Bernardo; Alves, Maria; Roque, Nádia (Phytotaxa, 2024)
Wedelia is the largest genus of Ecliptinae (Heliantheae, Asteraceae), comprising about 110 species. The Brazilian Cerrado is a highly threatened phytogeographic domain, which harbors the richest flora in the world among other savannas. A new subshrubby species of Wedelia was revealed occurring in the central part of Cerrado and is herein described as W. tenuinervia. This new species resembles W. foliacea in vegetative traits but differs mainly by having leaves with brochidodromous venation, pistillate ray flowers, glandular trichomes on the abaxial surface of the leaf blade, corolla lobes and apical anther appendages, phyllaries abaxial surface strigillose and disc cypselae 4–5-angled, keeled at the angles, without basal scars or elaiosomes, and carpopodium inconspicuous (vs. acrodromous venation, neuter ray flower, abaxial surface of the leaf blade, corolla lobes and apical anther appendage lacking glandular trichomes, phyllaries abaxial surface setose or glabrescent, and disc cypselae biconvex, not keeled, with basal scars or elaiosomes, and carpopodium in two plates or one shallowly lobed). Among the species with pistillate ray flowers, W. tenuinervia can be morphologically related to W. oligocephala, differing mainly by the membranaceous leaf blades with flat margins, brochidodromous venation, and solitary capitula (vs. subcoriaceous leaf blades with revolute margins, acrodromous venation and capitula in dichasia). Illustrations, comments, a preliminary conservation status, and the typification of W. foliacea’s synonyms are proposed.